2019
DOI: 10.1002/cncr.32451
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination, trust in physicians, and prolonged symptom duration before ovarian cancer diagnosis in the African American Cancer Epidemiology Study

Abstract: Background Discrimination and trust are known barriers to accessing health care. Despite well‐documented racial disparities in the ovarian cancer care continuum, the role of these barriers has not been examined. This study evaluated the association of everyday discrimination and trust in physicians with a prolonged interval between symptom onset and ovarian cancer diagnosis (hereafter referred to as prolonged symptom duration). Methods Subjects included cases enrolled in the African American Cancer Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Thirteen papers highlighted the influence of symptom knowledge (20) Five studies reported an association between demographic factors and HSB (29) (15) (27) (30) (22) Multiborbidity increased delay (30) as did a divorced or widowed marital status (30).…”
Section: Patient Factorsmentioning
confidence: 99%
“…Thirteen papers highlighted the influence of symptom knowledge (20) Five studies reported an association between demographic factors and HSB (29) (15) (27) (30) (22) Multiborbidity increased delay (30) as did a divorced or widowed marital status (30).…”
Section: Patient Factorsmentioning
confidence: 99%
“… 49 , 51 , 91 , 92 Individual- and group-level (eg, family or social network) barriers include cancer fear and stigma, poor health literacy, lack of trust in healthcare providers, and low expectations or perceptions regarding healthcare access or quality. 3 , 93 - 98 Such barriers have been associated with demonstrably longer intervals to help-seeking for possible cancer symptoms 99 , 100 and advanced stage at diagnosis among those diagnosed with cancer. 101 , 102 …”
Section: Prompt Help-seeking For Symptomsmentioning
confidence: 99%
“…To identify chronic disability, we began with NCHS algorithms capturing limitations in body functions and activity and participation difficulties. 22 These algorithms use responses from the Adult Health Status and Limitations module in the Sample Adult Core questionnaire. Supplemental eAppendix 1 (available with this article at JNCCN.org) presents the question stems and description of response categories.…”
Section: Chronic Disability Indicatorsmentioning
confidence: 99%
“…disparities also face delayed cancer diagnoses. 21,22 Diagnostic overshadowing-when clinicians erroneously attribute cancer signs and symptoms to the patient's underlying disability-can potentially delay cancer diagnoses. 23 This research explored associations between cancer and disability, focusing on 4 cancers that may present with nonspecific symptoms that could be conflated with aspects of disability.…”
Section: Introductionmentioning
confidence: 99%